Dehydroabietic acid attenuates atherosclerosis in apolipoprotein E-deficient mice and VCAM-1 expressions in-vitro - Liang, Xiao; Wu, Yan (Penerbit Universiti Kebangsaan Malaysia, 2022)
Dehydroabietic acid (DHA) is an analog of abietic acid (AA) for cardiovascular disease prevention, known to act pharmacologically against aging, inflammation, bacterial infections and cancer. The current research investigated the molecular mechanisms of DHA on the adhesiveness of endothelial leukocytes and activation of NF-κB in TNF-α treated HAEC and ApoE−/− mice in experimental atherosclerosis. The HAECs were tested for toxicity using MTT assay at various DHA concentrations. The cell-surface expression of CAM against endothelial leukocyte adhesion molecule-1, ICAM -1, or human VCAM-1 was determined by the ELISA test, followed by western blot analysis. Endothelial cell-leukocyte adhesion assay involving U937 cells was carried out followed by the determination of NF-κB p65 expression. ApoE−/− mice were fed with a high cholesterol diet every day followed by oral administration of DHA (10 and 20 mg/kg/day). The DHA (5 and 10 mM) substantially reduced (p < 0.05) human (U937) cell lines binding to TNF-α activated human endothelial aortic cells. The assays involving the 32P-labelled NF-kB as a probe demonstrated that DHA pre-treatment decreased the shifted bands density following the stimulation of TNF-α. Nuclear extracts immune blot assessment and immune fluorescence staining showed a significant decrease (p < 0.05) in the NF-κB p65 concentration in the nuclei with DHA treated human endothelial aortic cells. Together these findings indicate that DHA inhibits nuclear trans localization of TNF-α-induced NF-κB p65, and thus considerably suppresses (p < 0.05) the VCAM-1 expression, which contributes to lower leukocyte adherence suggesting that DHA helps in preventing inflammatory atherosclerosis in vivo.